2000
DOI: 10.1128/jvi.74.5.2186-2192.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human CD4+T-Cell Clones Recognizing Conserved and Variable Epitopes of the Lassa Virus Nucleoprotein

Abstract: T cells must play the major role in controlling acute human Lassa virus infection, because patients recover from acute Lassa fever in the absence of a measurable neutralizing antibody response. T cells alone seem to protect animals from a lethal Lassa virus challenge, because after experimental vaccination no neutralizing antibodies are detectable. In order to study human T-cell reactivity to single Lassa virus proteins, the nucleoprotein (NP) of Lassa virus, strain Josiah, was cloned, expressed in Escherichia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 33 publications
5
102
1
Order By: Relevance
“…It has previously been shown that during acute LCMV infection, functional CD4 ϩ T cell responses led to effective CTL responses and viral clearance (8,39,58). Interestingly, in the case of the related Lassa fever virus, seropositive individuals from endemic areas have strong memory CD4 ϩ T cells responses against the virus (59,60). In the case of HIV infection, strong CD4 ϩ T cell responses are detected in individuals who are treated with antivirals early in the course of infection, suggesting that CD4 ϩ T cell responses can be maintained if viral replication is contained (5,61,62).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that during acute LCMV infection, functional CD4 ϩ T cell responses led to effective CTL responses and viral clearance (8,39,58). Interestingly, in the case of the related Lassa fever virus, seropositive individuals from endemic areas have strong memory CD4 ϩ T cells responses against the virus (59,60). In the case of HIV infection, strong CD4 ϩ T cell responses are detected in individuals who are treated with antivirals early in the course of infection, suggesting that CD4 ϩ T cell responses can be maintained if viral replication is contained (5,61,62).…”
Section: Discussionmentioning
confidence: 99%
“…LV infection in humans seems to be controlled primarily by T-cell responses. Memory CD4 ϩ T cells directed against the viral nucleoprotein and glycoproteins circulate in LV-seropositive subjects (66,67), whereas neutralizing antibodies are detected at low titers only after recovery, and the production of specific immunoglobulin G (IgG) is not correlated with recovery (39). Furthermore, T-cell responses, but not antibody production, are correlated with protection of NHP against a lethal LV challenge after immunization and with the survival of naïve animals with LF (7,26,33).…”
mentioning
confidence: 99%
“…Humoral responses cannot control viral replication and the appearance of specific IgG in patients and infected monkeys is not correlated with recovery (11,12). The induction of cellular responses specific for viral glycoproteins protects nonhuman primates from a lethal challenge (12), and memory CD4 ϩ T cell responses against NP have been demonstrated in seropositive endemic subjects (13). In contrast, severe LV infections seem to be associated with high levels of viremia and immunosuppression.…”
mentioning
confidence: 99%